2015
DOI: 10.1111/sms.12403
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular and athletic performance following core strength training in elite youth soccer: Role of instability

Abstract: Cross-sectional studies revealed that inclusion of unstable elements in core-strengthening exercises produced increases in trunk muscle activity and thus potential extra stimuli to induce more pronounced performance enhancements in youth athletes. Thus, the purpose of the study was to investigate changes in neuromuscular and athletic performance following core strength training performed on unstable (CSTU) compared with stable surfaces (CSTS) in youth soccer players. Thirty-nine male elite soccer players (age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
0
14

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 41 publications
7
112
0
14
Order By: Relevance
“…For example, a 9-week core training programmed by Prieske et al (2016) indicated that there were significant improvements in sprint time and kicking performance (25). Our results are also consistent with Stray-Pedersen et al Tse, McManus, and Masters (2005) examined the effect of 8-week core endurance training program on college age rowers and found no improvement in the 40-m sprint, overhead medicine-ball throw or2000-m maximum rowing test.…”
Section: Discussionsupporting
confidence: 88%
“…For example, a 9-week core training programmed by Prieske et al (2016) indicated that there were significant improvements in sprint time and kicking performance (25). Our results are also consistent with Stray-Pedersen et al Tse, McManus, and Masters (2005) examined the effect of 8-week core endurance training program on college age rowers and found no improvement in the 40-m sprint, overhead medicine-ball throw or2000-m maximum rowing test.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have already examined the effects of core stabilization training on muscle strength, jump height, and various athletic performances in trained individuals (e.g., Prieske et al 2016a). Among these findings, some studies have reported that, as shown in the current study, the effects of core stabilization training on the strength capability of trunk or limb muscles vary with muscles examined even within the same body segments (Hoshikawa et al 2013;Prieske et al 2016b;Stanforth et al 1998). For example, Hoshikawa et al (2013) observed a significant gain in hip extension torque, but not in hip flexion torque.…”
Section: Changes In Muscle Strength and Maximal Lifting Powermentioning
confidence: 63%
“…For example, Hoshikawa et al (2013) observed a significant gain in hip extension torque, but not in hip flexion torque. Furthermore, Prieske et al (2016b) and Stanforth et al (1998) observed a strength improvement in trunk extension, but not in trunk flexion. In addition, it is known that core stabilization training has produced significant gains in muscle strength, assessed by maximum load which can be lifted in a given repetition, during multi-joint moments (right).…”
Section: Changes In Muscle Strength and Maximal Lifting Powermentioning
confidence: 93%
“…Core stabilization exercise and training have recently received remarkable attention and been reported to improve athletic performance such as sprint running and jump (Hoshikawa et al 2013;Jamison et al 2012;Prieske et al 2016). Although it is considered that a strong and stable trunk is beneficial for achieving high sport performances by providing a foundation for greater force production by limbs (Kibler et al 2006;Willardson 2007), the precise mechanism for the improvement in athletic performance remains unclear.…”
Section: Discussionmentioning
confidence: 98%